Frequency and factors associated with foregone and delayed medical care due to COVID‐19 among nonelderly US adults from August to December 2020. Issue 1 (15th December 2021) - Giannouchos, Theodoros V.; Brooks, John M.; Andreyeva, Elena; Ukert, Benjamin
Abstract: Objectives: To estimate the frequency and factors associated with foregone and delayed medical care attributed to the COVID‐19 pandemic among nonelderly adults from August to December 2020 in the United States. Methods: We used three survey waves from the Urban Institute's Household Pulse Survey (HPS) collected between August 19–31, October 14–26 and December 9–21. The final sample included 155, 825 nonelderly (18–64) respondents representing 135, 835, 598 million individuals in the United States. We used two multivariable logistic regressions to estimate the association between respondents' characteristics and foregone and delayed care. Results: The frequency of foregone and delayed medical care was 26.9% and 35.9%, respectively. Around 60% of respondents reported difficulties in paying for usual household expenses in the last 7 days. More than half reported several days of mental health issues. The regression results indicated that foregone or delayed care were significantly associated with difficulties in paying usual household expenses ( p  < 0.001), worse self‐reported health status ( p  < 0.001), increased mental health problems ( p  < 0.001), Veterans Affairs ( p  <0.001) or Medicaid ( p  = 0.003) coverage compared to private healthcare coverage, and older age groups. Individuals who participated in the latter two waves of the survey (October, December) were less likely to report foregone and delayed care compared to those who participated in Wave 1 (August). Conclusion: Overall, the frequency of foregone and delayed medical care remained high from August to December 2020 among nonelderly US adults. Our findings highlight that pandemic‐induced access barriers are major drivers of reduced healthcare provision during the second half of the pandemic and highlight the need for policies to support patients in seeking timely care.